Effect of Different Floor Types on Growth Performance and Feed Conversion Ratio of Mehsana Goat Kids - Patel, Jigar V.; Chauhan, Haresh D; Srivastava, Amit Kumar; Pawar, Mahesh M; Patel, Vikram K (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was done to evaluate the effect of different floor types on growth performance and feed conversion ratio of weaned Mehsana  goat kids for a period of 84 days. Twenty-seven weaned (3 months old) Mehsana goat kids having nearly identical body weights (10-12  kg) were randomly divided into three uniform groups having 9 kids (4 males and 5 females) in each group and reared on three different  types of floors, viz., group A: katcha floor, B: bricks floor, and C: concrete floor. All the kids were reared under standard management  system of goat rearing with strict hygiene and various parameters of production performance were recorded. Mean body weights in  kids of groups A, B and C were 13.56±0.25, 13.60±0.26, and 13.87±0.27 kg, respectively. The corresponding average daily body weight  gains were 35.89±2.74, 34.08±2.24, 39.23±4.10 g/day and feed conversion ratio 09.95±0.70, 08.99±0.52, 08.92±0.81, respectively. The  differences among treatment groups were found non-significant for all three parameters. Incidences of disease occurrence and parasitic  infestation were not noticed in kids of any group. It may be concluded that provision of different floor types, viz., katcha, bricks and  concrete had no significant effect on growth performance, feed conversion ratio, disease incidence and parasitic infestation in the  Mehsana kids. Further, from the study it may be inferred that economically weaker farmers may rear their kids on katcha floor with  strict hygiene and attain the growth rate at par with other flooring systems.
Keywords: Floor types; Growth performance; Feed conversion ratio; Mehsana goat kids